Instrumentación de un refrigerador doméstico 372 LRT F380G TMF para determinar el comportamiento del consumo energético en diferentes condiciones operativas de funcionamiento.Instrumentación de un refrigerador doméstico 372 LRT F380G TMF para determinar el comportamiento del consumo energético en diferentes condiciones operativas de funcionamiento. (2023)
This undergraduate thesis is related to specific objective 1 of a Research Project VCTI2024-1 on the actual performance of domestic refrigerators. The energy consumption value of a domestic refrigerator displayed on energy efficiency labels is the result of a set of internationally standardized measurements in laboratories. Research shows that this type of consumption is significantly influenced by real operating conditions. The objective of this work is the instrumentation of a domestic refrigerator to measure hermodynamic and electrical variables that will allow determining the behavior of energy consumption under different operating conditions. As a result, instrumentation was carried out with 16 sensors for external and internal temperatures, 2 for ambient temperature and relative humidity, voltage, current, frequency, power factor, instant and hourly consumption, complying with the stipulated standards by measuring it through a previously developed IoT-ESP32 device.